2014
DOI: 10.3892/ijo.2014.2246
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol induces autophagic and apoptotic death in gastric carcinoma cells

Abstract: Abstract. Despite conflicting results, there is evidence to suggest an inverse link between total body cholesterol levels and the risk of certain malignancies. Based on previous reports, this phenomenon appears to vary with cancer site, and, in particular, more consistent data on inverse relations was reported in the risk of gastric cancer. In the current study, the effect of cholesterol on gastric cancer cell viability was examined using an in vitro cell culture system. Addition of cholesterol in culture medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…While it did not influence MAP1LC3B mRNA expression, it did reduce LC3B-II, likely as a result of the absence of ATG5, a key component of the LC3B-II binary complex. To corroborate our findings, previous studies have shown the relationship between cholesterol synthesis or SREBP2 and autophagy [37,38]. SREBP2 directly binds to the promoter of several murine autophagy genes, such as Map1lc3b, Atb4b, and Atg4d, and SREBF2 knockout disrupts autophagosome formation in nutrient starvation in mouse models [37].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While it did not influence MAP1LC3B mRNA expression, it did reduce LC3B-II, likely as a result of the absence of ATG5, a key component of the LC3B-II binary complex. To corroborate our findings, previous studies have shown the relationship between cholesterol synthesis or SREBP2 and autophagy [37,38]. SREBP2 directly binds to the promoter of several murine autophagy genes, such as Map1lc3b, Atb4b, and Atg4d, and SREBF2 knockout disrupts autophagosome formation in nutrient starvation in mouse models [37].…”
Section: Discussionsupporting
confidence: 89%
“…SREBP2 directly binds to the promoter of several murine autophagy genes, such as Map1lc3b, Atb4b, and Atg4d, and SREBF2 knockout disrupts autophagosome formation in nutrient starvation in mouse models [37]. Gastric cancer cells also represent a case where cholesterol supplement in the culture media decreased cell viability and clonogenicity via both autophagy and apoptosis [38]. In our results, it is not clear whether autophagy was induced by direct activation via SREBF2 binding to the promoters of autophagy genes or by cholesterol supplement for autophagosome formation.…”
Section: Discussionmentioning
confidence: 99%
“…3D-E). Although the mitochondrial dysfunctions induced by cholesterol may promote apoptosis through the intrinsic pathway, the contribution of the extrinsic pathway of apoptosis induced by cholesterol through the activation of death receptors cannot be ruled out [45]. In addition to the protection against cholesterol-induced apoptosis by the prevention of mitochondrial dysfunction and cytochrome c release, QUE may exert protective effects by increasing Sirt1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The current treatments for gastric cancer include surgery, chemotherapy, radiotherapy, thermal therapy, immune therapy, and Chinese herbal treatment. However, due to the difficulty in diagnosing gastric cancer at an early stage, the prognosis with the current treatment options is often poor (4,5). Therefore, it is necessary to identify novel agents that more effectively treat advanced gastric cancer.…”
Section: Introductionmentioning
confidence: 99%